Membaca Pemikiran Ulrich Zwingli Tentang Reformasi Gereja (Sebuah Penelusuran Sejarah Gereja Hingga Sekarang ini) - Yosef, Hery Budi (Pusat Studi Pentakosta Indonesia, 2021)
This journal examines the historical description of Ulrich Zwingli's thoughts on church reform, especially after Martin Luther. And the results of the research provide new thinking that was left behind towards the reforms at that time. Though doctrinal thought began to move away from the papal hierarchy, but there are still things that were maintained by the reformers, and until now in the modern era it seems to be running (held), namely the practice of infant baptism, and the concept of the relationship between church and state. It's just that the results of this research are not more there, because the focus is solely on searching. There are many other sources that review Zwingli's actions in his involvement in removing other groups of believers (read: Anabaptists) from the church decisions that he fought for after the reformation. Because the concrete evidence has not shown the accuracy of the event, the author only focuses on his thoughts, specifically confronting his thoughts with the previous proclaimer of reform, namely Martin Luther. In this study, the background of the character, Zwingli's movement in Switzerland in an effort to reform the church will also be described successively as an extension of the previous important figures. In another section, Zwingli's thoughts which are the reasons for the reform of the church will be presented, Zwingli is slightly different from his predecessors in post-reform theology from Luther's. This journal uses a descriptive-historical qualitative approach, it is said that because the author examines it by tracing the sources contained in the literature regarding the characters studied, and linking them to the church today. Of course there will be limitations in the study, that's why the author hopes that there will be further research on this church figure, especially in other studiesJurnal ini mengkaji uraian historis terhadap pemikiran Ulrich Zwingli mengenai reformasi gereja khususnya setelah Martin Luther. Banyak sumber yang mengulas tentang sepak terjang Zwingli dalam keterlibatannya menyingkirkan kelompok orang percaya lainnya (baca: Anabaptis) dari ketetapan gereja yang diperjuangkannya pasca reformasi. Oleh sebab bukti-bukti konkrit belum menunjukkan keakuratan terhadap pristiwa tersebut, penulis hanya menyoroti pemikiran-pemikirannya, secara khusus mengkonfrontasikan pemikirannya dengan proklamator reformasi sebelumnya, yakni Martin Luther. Dalam kajian ini juga akan dipaparkan secara berturut-turut tentang latar belakang tokoh, pergerakan Zwingli di Swiss dalam upaya pembaharuan gereja sebagai perluasan dari tokoh-tokoh penting sebelumnya. Di bagian lain pemikiran-pemikiran Zwingli yang menjadi alasan reformasi gereja akan dipaparkan, Zwingli sedikit berbeda dengan pendahulunya dalam berteologi asca reformasi. Jurnal ini menggunakan pendekatan kualitatif deskritif – historis, dikatakan demikian karena penulis mengkaji dengan menelusuri sumber-sumber yang terdapat di literartur mengenai tokoh yang diteliti, dan mengkaitkan kepada gereja di masa kini. Tentunya aka nada keterbatasan dalam pengkajiannya, itu sebabnya penulis berharap aka nada penelitian lanjut terhadap tokoh gereja ini, khususnya dalam kajian yang lain.